WebMic and Companion Manual of Histology Exercises (Out of Print) - Robert Ogilvie (Association of American Medical Colleges, 2005)
Abstract Introduction WebMic is a web-based interactive virtual microscope that resembles the use of a real microscope. It is a Java program that includes 1300 histological images digitized at different magnifications, 750 labeled (annotated) structures, and 1400 textual comments that concisely describe labeled structures. The included traditional histological information covers the preparation of samples for microscopy, the histology of tissues, and the histology of organs. The goals of the companion manual are to: (1) direct the student to important structures, (2) provide a detailed step-by-step guide for examination of each specimen at several magnifications, and to summarize, (3) encourage review of what has just been covered. Methods The user interface allows scanning of specimens in a manner similar to using a microscope and glass slides. However, unlike when using a light microscope, the image being scanned and the magnified area of the scan are displayed simultaneously. The specimens in WebMic can be selected with or without important structures labeled. Structural dimensions can be measured. Results WebMic also includes two forms of self-assessment. There are 2 years of feedback from nearly 140 medical students each year in which the rating of WebMic and the Companion Manual of Histology Exercises are rated very highly. Discussion With WebMic, students can learn the microscopic architecture of the human body without the use of glass slides and the microscope, and that they can transfer their digital/virtual learning to the real glass slide and microscope. Practical examination scores confirm its success as a resource for learning practical histology independent of time, place, and faculty.